Does High School STEMM Career Coursework Align With College Employment?. Issue 3 (March 2023) - Gottfried, Michael; Freeman, Jennifer A.; Odle, Taylor K.; Plasman, Jay S.; Klasik, Daniel; Dougherty, Shaun M.
Background/Context: Career and technical education (CTE) coursework in science, technology, engineering, mathematics, and medical/health (STEMM) fields has been supported by policy makers as a way to align the secondary-to-postsecondary-to-career pipeline. Yet, in the research, the focus has been on whether STEMM CTE coursetaking in high school predicts college-going or whether it predicts employment for non–college goers. Little attention has been paid to whether STEMM CTE coursetaking in high school aligns with college employment opportunities. Purpose/Objective/Research Question/Focus of Study: This study investigates the relationship between one promising educational practice—STEMM career and technical education (STEMM CTE) coursetaking—and outcomes along students' college employment pathways. Specifically, we asked the following research questions: Does taking more STEMM CTE courses in high school link to "general" college employment outcomes? Does taking more STEMM CTE courses in high school link to "STEMM-specific" college employment outcomes? How do these relationships vary across important student subgroups, namely, those identified by the National Science Foundation as traditionally underrepresented in STEMM fields: low-income students, students with learning disabilities, women, and Black and Hispanic students? Research Design: We relied on data from the High School Longitudinal Study of 2009 (HSLS). Administered by the National Center for Education Statistics (NCES), HSLS is the most current, nationally representative data set that follows a cohort of more than 20, 000 ninth-grade students across the United States throughout high school and after graduation. Our regression analyses relied on data collected during the baseline year school-level survey (2009), the high school transcript update (2013), and student-level surveys from all four data-collection waves (2009, 2012, 2013, 2016). Conclusions/Recommendations: Using these national data, we find that taking more STEMM CTE courses was associated with a higher chance of having a STEMM job during college and having higher expectations for future STEMM employment, though not with general employment outcomes such as wages. The findings were different for students from some underrepresented backgrounds in STEMM fields, and implications are discussed.